O estudo da Religião da Grande Deusa nas escrituras indianas e o Canto I do Devi Gita. - Bianchini, Flávia (2013)
The subject of this dissertation is the religion of the Great Goddess in Indian scriptures, especially in the first canto of Devi Gita. This religion, belonging to Hinduism, presents itself as a devotional movement called Saktism. Its roots lie in the ancient Indian Vedic tradition, but it only became an independent movement, with its own original concepts, in the Medieval period of India. This study presents a vast outlook of the development of Saktism, from the Vedic age to the medieval Tantric Indian period, presenting information on the female deities and about other fundamental topics for the understanding of the religion of the Great Goddess. This dissertation culminates with a translation and commentary of canto I of the Devi Gita, a work belonging to the Devi Bhagavata Puraa. This scripture is recognized as an important source leading to the recognition of Saktism as an independent cult, and it is the oldest extant work where the Indian Goddess is presented as the supreme deity, as the Ultimate Reality and as the source of all creation.